Determination of nicotine in saliva, urine and wastewater samples using tantalum metal organic framework pipette tip micro-solid phase extraction. Issue 48 (28th November 2019) - Rezaei Kahkha, Mohammad Reza; Kaykhaii, Massoud; Sargazi, Ghasem; Kahkha, Batool Rezaei
Abstract : A novel tantalum metal organic framework (Ta-MOF) was synthesized by a microwave assisted reverse micelle procedure, and it was used as a sorbent for pipette tip micro-solid phase extraction of nicotine from biological and environmental samples. Abstract : A novel tantalum metal organic framework (Ta-MOF) was synthesized by a microwave assisted reverse micelle procedure, and it was used as a sorbent for pipette tip micro-solid phase extraction of nicotine from biological and environmental samples. Several parameters that influence the extraction efficiency, such as the amount of sorbent, the volumes of sample solution and eluent solvent, the type of eluent, and the number of draw/eject cycles of sample solution and eluent solvent, were studied and optimized. The results showed that the highest extraction efficiency was obtained when 5 mg Ta-MOF was placed into a 20 μL pipette tip and 3500 μL of 5 mg L −1 nicotine solution aspirated and dispensed over the sorbent after 15 cycles. The adsorbed nicotine was washed from the sorbent using 15 μL of methanol/ammonia solution as an eluent solvent with 20 draw/eject cycles. The linear dynamic range of this method was between 2 and 3000 μg L −1 and the limit of detection and the limit of quantification were 0.7 and 4.8 μg L −1, respectively. Intraday and interday precision expressed as relative standard deviation were good and found to be 2.7% and 5.2%, respectively. Finally, the method was successfully applied for the analysis of nicotine in six real samples of human saliva, urine and wastewater.